CONSTITUTIONAL DIAGNOSIS A NATURAL TOOL TO RECOGNIZE DISEASE IN ELECTROHOMOEOPATHY - Kamalakanta Nayak,; Manoj Kumar Mahala, (The Bioscan, 2025)
Self-healing is best healing. Everybody have self-healing properties from the onset of life. Responsible performance of body constituents on the way of natural maintenance renders good health. Any disturbance in the natural maintenance of body constituents indicates a disease. So performance of the constituents is the responsible factor behind health and disease. Diagnosis of disease is always task able for physicians. Body naturally maintains through air, water and the food grains. Blood is the only potentive fluid, which contains these potentive matters and transports them to nook and corner of the body for cellular absorption and after absorption it excretes cellular waste, unabsorbed matters and self secretions through its derivative lymph. Performance of the constituents indicates the constitution of disease. Body is a composition of solid and liquid constituents. Liquid: -Blood and Lymph Solid:- The whole tissue structure. All the solid parts the tissue stricture maintains through the two basic constituents Blood and Lymph, on the way of absorption, self-secretion, and excretion. Electrohomoeopathic principle for diagnosis of disease emphasizes more on the constitutions. Sheath of disease can be recognized very easily as to the performance of the constituents. If it is within the circulation of the blood more, the constitution is sanguine and when the lymphatic circulation disturbs more then it relates to lymphatic constitution. When the two basic constituents disturbs more and become unable to perform well as to their responsibility, depending structural units the tissue structure disturbs more and here the constitution is mixed.